Renal function of workers with low-level cadmium exposure. - Verschoor, M; Herber, R; van Hemmen, J; Wibowo, A; Zielhuis, R (Scandinavian Journal of Work, Environment & Health, 1987)
The influence of occupational exposure to cadmium on renal function was examined in 27 male cadmium workers from plants with second-degree usage of cadmium. The levels of cadmium in the blood and urine and various protein concentrations in the urine and serum were determined. The urinary levels of beta 2-microglobulin, retinol-binding protein, and N-acetyl-beta-D-glucosaminidase were statistically significantly increased in workers with urinary cadmium levels above 50 nmol/l. SDS-PAGE electrophoresis with silver staining is probably a sensitive indicator of the early effects of cadmium on protein excretion. The currently recommended biological exposure limits may have to be lowered.